Knowledge, attitudes, and practices of Lebanese licensed dietitians regarding hyperphosphatemia management in patients undergoing hemodialysis in a Lebanese Governorate - H. Mannan; E. Issa; R. Attieh; Y. Sacre (BMC Nephrology)
Abstract Background Hyperphosphatemia is deemed to be an asymptomatic silent killer, its high prevalence in patients undergoing hemodialysis (HD) is correlated mainly with malnutrition and mortality. Dietitian’s renal nutrition education has a major impact on chronic kidney disease patients’ knowledge, and attitude towards nutrition guidelines. However, a large number of factors are acting as barriers to the appropriate practices of Lebanese dietitians in renal therapy. This study evaluated the knowledge, attitudes, and practices (KAP) of licensed dietitians (LDs) regarding hyperphosphatemia management in patients undergoing HD. Methods A total of 408 LDs from Mount-Lebanon Governorate in Lebanon participated in this study. A 52-item online questionnaire was used to assess nutritional phosphorus’ KAP of all LDs, in compliance with dietetic practices with KDOQI guidelines updated version 2020 and identified the factors preventing dietitians from dealing with renal patients undergoing HD, e.g., nutrition care. The data was analyzed using SPSS version 25. Results There was a significant association between KAP levels, and almost all sociodemographic characteristics evaluated. Only 2% of dietitians applied all KDOQI guidelines, 64% attained poor and moderate knowledge, and 60% had a positive attitude towards renal care. Working in a clinical field was a common predictor of positive knowledge (adjusted OR = 2.453, 95% CI 1.244–4.836), positive attitude (adjusted OR = 1.900, 95% CI 1.300–2.541) and positive practice (adjusted OR = 0.192, 95% CI 0.184–0.491) while HD/hospital-based field increased the odds for positive knowledge (adjusted OR = 4.520, 95% CI 1.189–17.182). LDs, compared to registered dietitians, had lower odds of positive knowledge (adjusted OR = 0.390, 95% CI 0.231–0.658) and positive attitude (adjusted OR = 0.270, 95% CI 0.154–0.471). Lack of training was the main reason preventing the appropriate dietetic practices regarding hyperphosphatemia management in patients undergoing HD. Conclusion The Ministry of Public Health (MOPH) should be asked to endorse the integration of renal nutrition programs in the Lebanese curriculum, to aid in the empowerment of dietitians from different backgrounds towards renal therapy, in order to enhance the knowledge and attitude regarding nutritional guidelines of poorly supported Lebanese patients undergoing HDhemodialysis. Other stakeholders may include the Syndicate of Dietitians in Lebanon.